Field study on adaptive thermal comfort in office buildings in Malaysia, Indonesia, Singapore, and Japan during hot and humid season. (15th November 2016) - Damiati, Siti Aisyah; Zaki, Sheikh Ahmad; Rijal, Hom Bahadur; Wonorahardjo, Surjamanto
Abstract: Thermal comfort studies are necessary in the early stage of building design, especially in tropical climates where buildings are exposed to solar radiation throughout the year. In this study, we aimed to determine the summer comfort temperatures in offices in Malaysia, Indonesia, Singapore, and Japan. Through field surveys during 2015, we collected 2049 responses from 325 occupants in 13 office buildings employing various ventilation modes, namely, free running (FR), mixed mode (MM), and mechanical cooling (CL). The results showed that the comfort range differed for each group of occupants under the different ventilation modes. The comfort operative temperatures in tropical climates are 25.7 °C, 24.9 °C, and 27.5 °C for the CL, FR, and MM ventilation modes respectively, whereas in Japan it is 25.8 °C for both CL and MM. The survey revealed that 97% of the responses in Japan were within the central three points of the TSV scale, but lower percentages were recorded in the other countries. In Singapore, 92.9% of the respondents were feeling either cold, cool, or slightly cool in their offices. In terms of adaptive behaviour, most of the occupants in Malaysia frequently used air-conditioning systems to maintain thermal comfort, while drinking cold beverages was more common in Indonesia and Japan. The high comfort temperature with MM ventilation could be influenced by the strong air movement and a wide range of adaptive options, such as opening windows and utilising air-conditioning systems. Highlights: Thermal comfort and ventilation modes in Malaysia, Indonesia, Singapore, Japan. The highest mean comfort temperature is 27.5 °C with mixed mode ventilation. Comfort temperatures were higher than local comfort guidelines, except in Japan. Respondents in Japan indicate higher comfort temperature in low humidity condition.